(untitled) (Journal of Architectural Design, 2022)
The article describes the device, the principle of operation and scope of load -griping devices designed to overload building goods and installation of structures in construction. The recommendations for the operation, device and selection of the main parameters of rental devices, static and dynamic, loads affecting the loading devices are presented.